The influence of physicochemical environment on the distribution and abundance of mangrove gastropods in Ngurah Rai Forest Park Bali, Indonesia - Ajie Imamsyah; I WAYAN ARTHANA; IDA AYU ASTARINI (Society for Indonesian Biodiversity, 2020)
Abstract. Imamsyah A, Arthana IW, Astarini IA. 2020. The influence of physicochemical environment on the distribution and abundance of mangrove gastropods in Ngurah Rai Forest Park Bali, Indonesia. Biodiversitas 21: 3178-3188. Ngurah Rai Forest Park is the widest mangrove ecosystem in Bali that close to the business center and tourism area. The strategic location of the Ngurah Rai Forest Park is estimated to produce anthropogenic waste that can disrupt the gastropod population and stability of the mangrove ecosystems. This study aims to analyze the mangrove density, distribution, and abundance of gastropods based on the quality of the biophysical environment. Mangrove data collection was carried out using a plot transect of 10 m x 10 m, 5 m x 5 m, and 1 m x 1 m. Meanwhile, samples gastropods were collected on a plot transect of 0.5 m x 0.5 m in plot transect of 5 m x 5 m. A total of 11 gastropods species and 6 mangrove species were recorded in this study. The dominant gastropods species found were Assiminea brevicula (28 ind/m2). Species mangrove of Sonneratia alba and Rhizophora apiculata found were in all study sites with tree density values of 1000 ind/ha. Subsequently, the ecological index calculation results show that the diversity index (H’) (2.89-3.2), evenness index (E) (0.87-0.93), and dominance index (C) (0.12-0.17). Based on the Principal Component Analysis (PCA) found was Assiminea brevicula spread on sand and silt substrates and adaptive to the temperature condition, salinity, pH, and dissolved oxygen. Furthermore, other analysis results showed that Cerithidea cingulata, Cerithidea quadrata, Littoraria articulata, and Littoraria scabra were found on clay substrate with high C-organic content. In conclusion, gastropods are evenly distributed and no species dominate the ecosystems.